BULK EXTRACTION OF RIVERBED MINERALS AND ITS IMPACT ON AGRICULTURAL CULTIVATION (International Journal of Food and Nutritional Sciences, 2022)
River water is the paramount in comparison to all other needs to exercise on-stream agriculture cultivation. Rivers deliver congenial quality of water which is integral for healthy cultivation, while benefitting the human race with other materials without upshot in overall development is unattainable. Due to blistering construction of roads, railway, and buildings etc. demand ample supply of riverbed minerals triggered the extraction of riverbed minerals at bulk. In fulfilling the demand of riverbed minerals mining mafia turned into myopic mode. They use big extraction machines in extraction process and work chiefly on night basis to rescind government intervention. Adoption of modern technology in extraction process gave birth to many harmful factors which affected on-stream agricultural, aquatic system, river morphology, river beauty and mainly the people who are living nearby the river. In connection with new challenges posed by riverbed mining the present study has made an attempt to analyze the impact of riverbed mining on agricultural productivity. In present study 5 mining hotspot villages have been taken under study under which 100 farmers were selected who do farming on nearby the river purposive sampling method. A well structured schedule was designed for the data collection purpose. After data collection Excel and SPSS software were used for descriptive and inferential analysis. Simple paired t test and ANOVA test were applied to test the hypothesis. The findings of the paper were drastic and needs immediate attention. The over use of technology caused bulk extraction of riverbed minerals which mainly ebb agricultural productivity and also diversify the cultivation practice. The changes occurred in the river morphology has bring a very hard challenge to farmers and has made them handcuffed and difficult to sustain the agriculture practice. The drop in the water level affected farmer’s irrigation system and the people who are living nearby river also witnessed fall in the supply of drinking water from their sources especially from their tube wells. The findings of the research foreground the complication and cascading nature of affects of riverbed mining on agricultural, as well as the exactingness and urgency of the challenge. Based on the execrable results found a set of suggestions are listed at the end of the paper to halt and minimize the affect of bulk extraction mining on agricultural productivity.